The folklore of carioca samba: memory, history and identity - Garcia, Tania da Costa [UNESP] (Univ Federal Uberlandia, 2017)
In younger nations, like the American ones, parallel to the popular-rural repertoire defined as national folklore, the urban popular music disseminated by mass media began to dispute space among the nationality-forming elements. To legitimate it as a representation of the national, it had to be folclorized, invent a tradition for it. This article analyzes how the construction and consecration of Rio de Janeiro samba as a symbol of Brazilianness takes place in three moments of the twentieth century. At first, in a less programmatic manner, by the memorialists; then, in 1930's Rio de Janeiro, followed by formalization of the discourse of preservation and nationalization of the Carioca musical past, in 1940-1950; eventually, in 1970-1980, with the Funarte (National Art Foundation) Department of Popular Music, manage by Herminio Bello de Carvalho, samba is officially declared as an expression of Brazilian culture.
Keywords: Popular music; samba; folklore